How does the Dorr classification of proximal femur affect the total hip arthroplasty of hemophilic patients: a retrospective study - Yichen Gong; Hua Huang; Hai Su; Haojin Zhou; Peijian Tong; Shuaijie Lv (Scientific Reports)
Abstract Patients with hemophilia (PWH) constantly suffer hemarthrosis due to the lack of coagulation factors, resulting in progressive deformity of the hip joint. Currently, there is a dearth of understanding on the unusual morphology of proximal femur in PWH. To explore how does the Dorr classification of proximal femur affect the total hip arthroplasty (THA) of PWH, we conducted a retrospective study on PWH with different Dorr classifications who underwent THA. The retrospective study comprises data of adult patients who received THA from 2018 to 2022 in the research center. Patients with a diagnosis of hemophilic arthritis and received THA were included and divided into three groups according to Dorr classification. The X-ray images were acquired before the surgery to determine the Dorr classification. The surgical time, surgical blood loss, laboratory examinations post-operation including hemoglobin (HB), total protein (TP), activated partial thromboplastin time (APTT), D-dimer (D2), C-reactive protein level (CRP), erythrocyte sedimentation rate (ESR), and functional evaluations 1 year after surgery including visual analogue scale (VAS), Harris hip score (HHS), range of motion (ROM) were collected. Kolmogorov–Smirnov test is used to test data normality, and t-test is performed by SPSS 20. P < 0.05 is considered statistically significant. 33 PWH are included in the study and have finished follow-up. All cases are male patients. Among the 33 hips, 19 (57.6%) are classified to Dorr A, and 12 (36.4%) are Dorr B, and only 2 (6%) are Dorr C. No significant difference is found in expanse, hospital stay, surgical time and total blood loss. PWH with Dorr A requires significant less coagulation factor than Dorr B and Dorr C. All Dorr types of hips present good recovery from the surgery according to the perioperative examinations including hemoglobin (HB), total protein (TP), activated partial thromboplastin time (APTT), D-dimer (D2), C-reactive protein level (CRP), erythrocyte sedimentation rate (ESR), and thigh circumference (TC). The 2-year follow-up demonstrates favorable functional rehabilitation according to functional evaluations including visual analogue scale (VAS), Harris hip score (HHS), and range of motion (ROM). In this study, we find that PWH tend to have higher prevalence of Dorr A than the general population. PWH with Dorr A requires smaller dosage to maintain the coagulation factor activity than the Dorr B and Dorr C. Additionally, all types of hip present favorable recovery after THA. Ultimately, the study supports that THA is an effective treatment for PWH with all Dorr classifications by alleviating the pain and improve the motor function.